Inhibitors of melanogenesis in B16 melanoma 4A5 cells from flower buds of Lawsonia inermis (Henna). Issue 13 (1st July 2015) - Nakashima, Souichi; Oda, Yoshimi; Nakamura, Seikou; Liu, Jiang; Onishi, Koko; Kawabata, Miki; Miki, Hisako; Himuro, Yugo; Yoshikawa, Masayuki; Matsuda, Hisashi
Graphical abstract